A novel derivative of the fungal antimicrobial peptide plectasin is active against Mycobacterium tuberculosis. (December 2018) - Tenland, Erik; Krishnan, Nitya; Rönnholm, Anna; Kalsum, Sadaf; Puthia, Manoj; Mörgelin, Matthias; Davoudi, Mina; Otrocka, Magdalena; Alaridah, Nader; Glegola-Madejska, Izabela; Sturegård, Erik; Schmidtchen, Artur; et al.
Abstract: Tuberculosis has been reaffirmed as the infectious disease causing most deaths in the world. Co-infection with HIV and the increase in multi-drug resistant Mycobacterium tuberculosis strains complicate treatment and increases mortality rates, making the development of new drugs an urgent priority. In this study we have identified a promising candidate by screening antimicrobial peptides for their capacity to inhibit mycobacterial growth. This non-toxic peptide, NZX, is capable of inhibiting both clinical strains of M. tuberculosis and an MDR strain at therapeutic concentrations. The therapeutic potential of NZX is further supported in vivo where NZX significantly lowered the bacterial load with only five days of treatment, comparable to rifampicin treatment over the same period. NZX possesses intracellular inhibitory capacity and co-localizes with intracellular bacteria in infected murine lungs. In conclusion, the data presented strongly supports the therapeutic potential of NZX in future anti-TB treatment.